Pengaruh Kompensasi, Lingkungan Kerja dan Budaya Organisasi Terhadap Kepuasan Karyawan Pengemudi Ojek Online GRAB Kota Malang - Muhammad Taufiq Annawawi; abd kodir djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of compensation, work environment and organizational culture on employee satisfaction of GRAB online motorcycle taxi driver in Malang. The population contained in this study amounted to 15,247 people and the Slovi (1960) was used to determine the research sample with a significance level of 0.1, and the sample size in this study was 99 people. Data analysis method used in this research is quantitative analysis method. Researchers in this case used questionnaire media and primary data. The survey used in this study is a direct and personal survey. The survey is given directly to respondents, who can choose one alternative answer available. Based on the survey result it can be seen that compensation, work environment and organizational culture greatly affect employee satisfaction of GRAB online motorcycle taxi employee in Malang.